Treatment of depression in diagnosed diabetes: common cause or detection bias?. Issue 6 (April 2014) - Manderbacka, K.; Jokela, M.; Sund, R.; Elovainio, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Background This study examined two competing hypotheses concerning the association between diabetes and treatment for depression: (1) the detection/ascertainment bias hypothesis suggesting that those with diabetes are more likely to be diagnosed with and treated for depression because of increased medical attention and (2) a hypothesis assuming that diabetes and depression share common underlying pathophysiological pathways. Method The study population included all persons aged 35–65 years in Finland with any record of type 2 diabetes in the national health and population registers from 1999 to 2002 and for whom register-based data on depression treatment (antidepressant medication use and hospitalizations for depression) were available at least 2 years before and after the diagnosis of diabetes (n = 18 217). Sociodemographic data were individually linked to the study population. Associations between diabetes diagnosis and time and indicators of depression care were assessed with population-averaged multilevel logistic models. Results Within the year following diagnosis diabetes, there was a 5% increase in antidepressant medication use but not in hospitalization for depression. The longitudinal change in antidepressant use over time was less steep after the diabetes diagnosis, and hospitalization risk decreased after the diagnosis. These associations between diabetes diagnosis and depression treatment were not modified by the participant's socio-economic position (SEP). Conclusions These findings support the common cause hypothesis that treatment for diabetes is beneficial to the prevention of depression rather than the detection/ascertainment hypothesis that individuals with diabetes have higher rates of depression because they receive more medical attention in general.